Phocoena phocoena subsp. phocoena Linnaeus 1758 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Phocoena phocoena subsp. phocoena Linnaeus 1758 Phocoena phocoena subsp. phocoena Linnaeus 1758, Syst. Nat., 10th ed., Vol. 1: 77. Type Locality: "Habitat in Oceano Europaeo, & Balthico." (= Baltic Sea, "Swedish Seas"). Vernacular Names: North Atlantic Harbor Porpoise. Synonyms: Phocoena phocoena subsp. americana Allen 1869; Phocoena phocoena subsp. communis Lesson 1827; Phocoena phocoena subsp. lineata Cope 1876. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 736, DOI: 10.5281/zenodo.7316519